Kepraktisan E-Modul Berorientasi Problem Based Learning untuk Melatihkan Keterampilan Metakognitif Peserta Didik pada Materi Laju Reaksi - Rina Ayu Puspita; Rusly Hidayah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This research is a research and development (Research and Development) that aims to develop an e-module oriented to Problem Based Learning (PBL) on the reaction rate material that is practically used in the learning process. The development model used is the 4D model consisting of four stages, namely Define, Design, Develop, and Disseminate. However, this study is limited to the Develop stage, which was tested on a limited basis at SMA Assa'adah Gresik. Data were obtained through student response questionnaires and learning activity observation sheets. The results of the analysis show that the e-module developed is classified as very practical. This is indicated by the results of the student response questionnaire which obtained a percentage of 96% with a very practical category, and is supported by the results of observations of student activities which also reached a percentage of 96% in the same category. Thus, this e-module is worthy of being used as an alternative effective and interactive learning media on the reaction rate material.